ChemInform Abstract: Synthesis of Some Novel Pyrazole‐Substituted 9‐Anilinoacridine Derivatives and Evaluation for Their Antioxidant and Cytotoxic Activities. Issue 4 (31st January 2013) - Kalirajan, R.; Muralidharan, V.; Jubie, S.; Gowramma, B.; Gomathy, S.; Sankar, S.; Elango, K.
Abstract A series of novel pyrazole‐substituted 9‐anilinoacridines are designed, synthesized and evaluated for their in vitro antioxidant and cytotoxic activity.